2022
DOI: 10.1111/jon.13023
|View full text |Cite
|
Sign up to set email alerts
|

Novel imaging markers for altered cerebrovascular morphology in aging, stroke, and Alzheimer's disease

Abstract: Background and Purpose: Altered brain vasculature is a key phenomenon in several neurologic disorders. This paper presents a quantitative assessment of the anatomical variations in the Circle of Willis (CoW) and vascular morphology in healthy aging, acute ischemic stroke (AIS) and Alzheimer's Disease (AD). Methods:We used our novel automatic method to segment and extract geometric features of the cerebral vasculature from MR angiography scans of 175 healthy subjects, which were used to create a probabilistic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Of 100 AIS patients, the occlusion sites were the Internal Carotid Artery (ICA) in 18, tandem ICA-MCA in 17, and M1 and M2 segments of the MCA in 46 and 19, respectively. We utilized our previously developed probabilistic cerebrovascular atlas of spatially co-registered cerebral vessel maps of 175 healthy adults (34). The atlas was labeled to denote the five major vascular territories: (1) the ICA, (2 and 3) the left and right MCA, (4) Anterior Cerebral Artery (ACA), and (5) the posterior cerebral artery (PCA) and basilar artery (BA), as illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 100 AIS patients, the occlusion sites were the Internal Carotid Artery (ICA) in 18, tandem ICA-MCA in 17, and M1 and M2 segments of the MCA in 46 and 19, respectively. We utilized our previously developed probabilistic cerebrovascular atlas of spatially co-registered cerebral vessel maps of 175 healthy adults (34). The atlas was labeled to denote the five major vascular territories: (1) the ICA, (2 and 3) the left and right MCA, (4) Anterior Cerebral Artery (ACA), and (5) the posterior cerebral artery (PCA) and basilar artery (BA), as illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We implemented a two-step approach for automatic stroke detection based on previous preliminary studies that showed a significant difference in cerebrovascular features between stroke patients and healthy subjects (32,34). In the first step, the presence of occlusion was determined by comparing the vessel density of the patient-specific vascular network with the cerebrovascular atlas using the total vessel length, volume, and the number of branches.…”
Section: Stroke Detection and Occlusion Localizationmentioning
confidence: 99%
See 3 more Smart Citations